2010
DOI: 10.1111/j.1939-3938.2009.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the effectiveness of aggression management training programs for psychiatric hospital staff

Abstract: The findings of this study suggest that relying too heavily on aggression management staff training will have limited effect on addressing the range of issues related to patient-perpetrated violence in psychiatric hospitals. Mental healthcare organizations must look beyond staff training if they are to achieve meaningful reductions in aggressive incidents and staff injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 45 publications
1
40
0
2
Order By: Relevance
“…No consideration was given to the extent and content of employee training and support. Studies and reviews are now available that deal with the effectiveness of training programmes in different healthcare sectors 38 45 46. It is not entirely clear as to whether training programmes can reduce the number of instances of violence, but cognitive knowledge and subjective confidence tend to have a positive effect on how staff cope with the experience of violence.…”
Section: Discussionmentioning
confidence: 99%
“…No consideration was given to the extent and content of employee training and support. Studies and reviews are now available that deal with the effectiveness of training programmes in different healthcare sectors 38 45 46. It is not entirely clear as to whether training programmes can reduce the number of instances of violence, but cognitive knowledge and subjective confidence tend to have a positive effect on how staff cope with the experience of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Fostering coping skills and resilience are now recommended components of AM training (30,31). Although there is ample guidance for designing AM training, scientific evidence proving its actual benefits is limited (32): a number of literature reviews synthesizing evidence on the effect of AM training point to predominantly low quality of research (33)(34)(35)(36)(37). In practice, AM training evaluation has been criticized for failing to go beyond "happy sheets", i.e., feedback forms filled in by course participants on completion of the training (25,32).…”
Section: Introductionmentioning
confidence: 99%
“…5, 1214 Instead, problematic resident behaviors are too often treated with psychotropic medications or restraint, while behavioral remedies are underutilized. 15–17 The limited research available on aggression management programs is focused on institutional settings, especially psychiatric units, with nurses identified as the population most at risk of violence.…”
Section: Introductionmentioning
confidence: 99%
“…15–17 The limited research available on aggression management programs is focused on institutional settings, especially psychiatric units, with nurses identified as the population most at risk of violence. 12, 18 In a meta analysis of 29 aggression management programs, which averaged 18 hours per year, Livingston et al, 12 reported that the aggression training programs lacked standardization, and may or may not reduce patient initiated violence, but they did appear to reduce use of restraint and coercive techniques by staff.…”
Section: Introductionmentioning
confidence: 99%